PREVENTION OF GASTRITIS AND STOMACH CANCER AMONG THE POPULATION - Ahmadaliyev Shokhruk Shukhratovich; Numonova Sayyora Salimjan daughter (European Science Publishing, 2024)
Maintaining the health of the population through measures aimed at timely detection and treatment of gastritis and stomach cancer in the population by introducing the method of gastroenterology examination and FGDS examination in rural family polyclinics. It is important to treat detected gastritis and refer stomach tumors to special oncologists.
Keywords: Gastritis, stomach tumors, gastroenterologist, FGDS, malignancy of stomach polyps, oncology.